The adaptive computation of far-field patterns by a posteriori error estimations of linear functionals - Monk, P; Suli, E (SIAM, 1998)
This paper is concerned with the derivation of a priori and a posteriori error bounds for a class of linear functionals arising in electromagnetics which represent the far-field pattern of the scattered electromagnetic field. The a posteriori error bound is implemented into an adaptive finite element algorithm, and a series of numerical experiments is presented.